Determining the incidence of interstitial pneumonitis and chronic kidney disease following full intensity haemopoetic stem cell transplant conditioned using a forward-planned intensity modulated total body irradiation technique. (May 2021) - Durie, Emily; Nicholson, Emma; Anthias, Chloe; Dunne, Emma M.; Potter, Mike; Ethell, Mark; Messiou, Christina; Brennan, Joy; Eagle, Sally; Talbot, James; Smyth, Gregory; Ingram, Westley; et al.
Highlights: FP IMRT has a low rate of idiopathic IP with only 4% ( n = 3) CTCAE grade ≥ 3. 30% developed IP due to any cause; evidence of an underlying infective cause was identified in 73%. Only 2 long term survivors developed CKD, 1 having thrombotic microangiopathy. NRM at 4 years was 16% and no patients had evidence of primary graft failure. Abstract: Purpose/Objective: Total body irradiation (TBI) remains a key component of conditioning for allogeneic haemopoietic stem cell transplant (HSCT), with interstitial pneumonitis (IP) and chronic kidney disease (CKD) important late sequelae. We undertook a retrospective service evaluation of TBI patients treated with a forward-planned intensity modulated radiotherapy technique (FP IMRT). Material/Methods: 74 adult patients were identified; all received step and shoot FP IMRT TBI, 14.4 Gy in 8 fractions over 4 days. Mean doses to the lungs and kidneys were 12–12.5 Gy. Toxicities were defined as per CTCAE v4.0: IP as multilobar infiltrates on CT with symptoms of dyspnoea, and renal dysfunction as an Estimated Glomerular Filtration rate (eGFR) < 60 ml/min/1.73 m 2 for > 3 months. Secondary endpoints were overall survival (OS), progression free survival (PFS), cumulative incidence of non-relapse mortality (NRM), relapse risk and of acute and chronic GvHD. Results: Patients received treatment for the following diagnosis: ALL/LBL ( n = 37); AML ( n = 33), CML-BC ( n = 2) and High grade NHL ( n = 2). The rate of IP due to any cause was 30%; positive microbiological evidence in 73% (16 /22). Idiopathic IP was seen in 8%, with only 4% ( n = 3) having IP Grade ≥ 3. Two (4%) of 52 long term survivors developed CKD, one with thrombotic microangiopathy. 4 year NRM was 16% (CI 11–32%); no treatment related deaths in matched sibling or umbilical cord blood HSCT. Conclusion: FP IMRT TBI, reducing dose to the lungs and kidneys, has lower rates of idiopathic IP and CKD compared to the literature. This technique is safe and effective conditioning for full intensity HSCT.